(untitled) (World Bulletin of Management and Law, 2026)
Small and Medium Enterprises (SMEs) are the backbone of developing economies like Nigeria, contributing approximately 48% to the nation’s GDP and employing nearly 84% of the workforce. Despite this critical domestic role, their participation in international trade is severely constrained, primarily due to inadequate access to trade finance and significant structural barriers. This study critically examines the relationship between trade finance accessibility and the internationalization capacity of Nigerian SMEs. It analyzes how specific financial instruments, institutional frameworks, and macroeconomic factors influence their ability to engage in cross-border trade. The research uses a mixed-methods approach, integrating quantitative data from 250 export-oriented SMEs across manufacturing, agribusiness, and services with qualitative interviews involving commercial banks, development finance institutions, and policy agencies. Econometric modeling tests the link between trade finance availability and SME export performance, while thematic analysis explores underlying behavioral and institutional constraints. The findings confirm that restricted access to essential trade finance instruments including letters of credit, pre- and post-shipment financing, and export credit guarantees, significantly impedes SMEs’ ability to enter and sustain foreign market operations. Key deterrents are information asymmetry, stringent collateral requirements, high interest costs, and a weak credit infrastructure. Conversely, SMEs with access to structured facilities and targeted financial literacy support show markedly higher internationalization, competitiveness, and revenue diversification. This study contributes a contextual framework to international business and development finance theory. It advocates for the development of targeted financial instruments, public–private credit guarantee schemes, and specialized capacity-building initiatives to enhance SME trade finance access and foster sustainable export growth in Nigeria